EFFECT OF SOME AGRICULTURAL PROCESS ON GROWTH AND YIELD OF SORGHUM (Sorghum bicolor L.) (ARTICLE REVIEW) - Rayan Al-Obady; Salim Ghazal; Waleed Al-Juheishy (Mesopotamia Journal of Agriculture)
Sorghum is one of the important cereal crops and its importance is due to its multiple uses, as it is used in human food and animal feed in the form of concentrated grains or green fodder, as well as entering into many industries such as starch, cellulose, alcohol, brooms, baskets and many handicrafts and others.  Sorghum is the most drought-tolerant summer field crop, but it is one of the crops  that stresses the soil as a result of depleting many nutrients, especially nitrogen. Therefore, fertilization is necessary, especially nitrogen, which is reflected in improving the quality of forage and increasing the dry matter yield .The growth and yield of sorghum is affected by many environmental, genetic and agricultural factors, in which the growth and yield are the sum of the effect of these factors combined, and that following modern methods in serving this crop is one of the main factors in improving yield productivity, and the most important of these factors is determining the best cultivar and optimal planting date and the recommended plant density and the best fertilization rate that gives the best yield and the least cost and damage.